Determination of Asenapine Maleate in Pharmaceutical and Biological Matrices: A Critical Review of Analytical Techniques over the Past Decade. (7th November 2022) - Kotak, Vishwa; Tanna, Nisha; Patel, Mrunali; Patel, Rashmin
Abstract: Asenapine maleate is a second-generation atypical antipsychotic agent used in the treatment of schizophrenia, a neuropsychiatric disorder. It is available as a fast-dissolving sublingual tablet to avoid extensive first-pass metabolism with higher bioavailability as compared to oral formulations. Although, the established therapeutic solutions do not sufficiently satisfy the patient's safety and efficacy needs. Thus, the core research emphasis is to investigate strategies to produce novel formulations with enhanced safety and efficacy. This necessitates the development of robust, precise, and accurate methods for quantification of asenapine maleate in different sample matrices. Given the foregoing information, the current analysis concentrates on the different analytical techniques used to assess asenapine maleate in bulk, pharmaceutical formulations, and biological specimens. Reverse-phase HPLC coupled with UV detection is a majorly (nearly 50% of papers investigated) used technique for the estimation of asenapine maleate in formulations. On the other hand, for its quantification in the biological matrix, hyphenated techniques using mass spectrometry are widely used. This critical review reveals different analytical methodologies, including spectrophotometric, chromatographic, capillary electrophoresis techniques reported from 2011 to 2020, for the measurement of asenapine maleate in various sample matrices. The information presented in this review would be useful in future research for robust analytical method development for asenapine maleate utilizing a more scientific and risk-based approach. Also, it would aid to minimize analytical failure as well as method fine-tuning throughout the product life cycle. Further, this review may also direct scientists toward the development of methodologies for green research.